The Effect of the Particle Size Reduction on the Biorelevant Solubility and Dissolution of Poorly Soluble Drugs with Different Acid-Base Character - Dóra Csicsák; Rita Szolláth; Szabina Kádár; Rita Ambrus; Csilla Bartos; Emese Balogh; István Antal; István Köteles; Petra Tőzsér; Vivien Bárdos; Péter Horváth; Enikő Borbás; et al. (MDPI AG, 2023)
Particle size reduction is a commonly used process to improve the solubility and the dissolution of drug formulations. The solubility of a drug in the gastrointestinal tract is a crucial parameter, because it can greatly influence the bioavailability. This work provides a comprehensive investigation of the effect of the particle size, pH, biorelevant media and polymers (PVA and PVPK-25) on the solubility and dissolution of drug formulations using three model compounds with different acid-base characteristics (papaverine hydrochloride, furosemide and niflumic acid). It was demonstrated that micronization does not change the equilibrium solubility of a drug, but it results in a faster dissolution. In contrast, nanonization can improve the equilibrium solubility of a drug, but the selection of the appropriate excipient used for nanonization is essential, because out of the two used polymers, only the PVPK-25 had an increasing effect on the solubility. This phenomenon can be explained by the molecular structure of the excipients. Based on laser diffraction measurements, PVPK-25 could also inhibit the aggregation of the particles more effectively than PVA, but none of the polymers could hold the nanonized samples in the submicron range until the end of the measurements.